1967
DOI: 10.1042/bj1030816
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the polydispersity in sedimentation patterns of rapidly labelled nuclear ribonucleic acid

Abstract: 1. A study was made of the sedimentation properties of purified preparations of the rapidly labelled RNA in the nucleus and the cytoplasm of the HeLa cell. The sedimentation of the rapidly labelled nuclear RNA was very sensitive to changes in ionic strength and bivalent cation concentration. Under the conditions usually used in sucrose-density-gradient centrifugation the rapidly labelled nuclear RNA showed extreme polydispersity, and much of it sedimented more rapidly than the 28s RNA. At low ionic strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1967
1967
1978
1978

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Thus, it would be advisable to obtain further independent evidence bearing on the polynucleotide chain lengths for the different preparations, particularly for the shorter pulse times. Bramwell and Harris (1967) have suggested that the mean polynucleotide lengths in rapidly labeled RNA preparations may be similar to those for rRNA, and this would be consonant with the present findings. It should be noted that the present estimates, being number-average values, could be different from weight-average estimates for these same preparations, and this will be an important consideration with rapidly labeled RNA specimens, just as it appears that it may be with rRNA specimens (Lane and Tamaoki, 1967).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it would be advisable to obtain further independent evidence bearing on the polynucleotide chain lengths for the different preparations, particularly for the shorter pulse times. Bramwell and Harris (1967) have suggested that the mean polynucleotide lengths in rapidly labeled RNA preparations may be similar to those for rRNA, and this would be consonant with the present findings. It should be noted that the present estimates, being number-average values, could be different from weight-average estimates for these same preparations, and this will be an important consideration with rapidly labeled RNA specimens, just as it appears that it may be with rRNA specimens (Lane and Tamaoki, 1967).…”
Section: Discussionsupporting
confidence: 90%
“…58 mCi/mmole) was purchased from New England Nuclear and diluted with cold steroid as indicated in table 3. The final membrane suspension was solubilized in 5 ml of scintillating fluid [6] and counted in a Packard Tri Carb Scintillator Counter.…”
Section: Methodsmentioning
confidence: 99%
“…This is in accordance with results of BALTUS and QUERTIER (1966) but in contrast to what is known of other organisms. Since it seems improbable that the ratio of 1 : 2 in Acetabularia is due to degradation under the conditions used, one has to consider an interconversion of the two components (BRAMWELL and HARRIS, 1967;HAR-RIS, 1968) or a peculiar structure of A cetabularia ribosomes. It proved difficult to avoid degradation of RNA during the preparation of RNA from enucleated Acetabularia (DILLARD and SCHWEIGER, 1969).…”
Section: C) Rnamentioning
confidence: 99%